Assessment moderation in large transnational units: a case study - Goldacre, Lisa; Briguglio, Carmela (Centre for Development of Teaching and Learning, 2008)
All students taking the Bachelor of Commerce course offered by Curtin Business School (CBS) are required to complete seven common or core units. This results in large student enrolments in first year units and a cOITesponding increase in the use of sessional staff to teach the cUITiculum. Additionally, CBS delivers these courses in various modes to many locations in metropolitan and regional Australia and to several offshore locations including Singapore, Malaysia, Mauritius and Vietnam. For each first year common core unit, there are approximately 1000 students enrolled at the West Australian campus and another 1000 enrolled at other locations or through distance education. The number in second semester is approximately half this.This paper describes a consensus moderation activity undertaken in a first year introductory law unit. This activity was part of a larger project to enhance the teaching and learning experience of first and second year business students. The aims of the activity were to train sessional staff in the area of assessment, assist tutors in providing feedback to students, ensure valid and equitable assessment through moderation and establish clear and accountable assessment processes for the development of assessment criteria and rubrics to inform students and for the appeals process. This paper will also briefly consider the literature regarding current thinking in assessment moderation, pmticularly in relation to transnational education. In conclusion, the paper reflects on the efficacy of the materials and processes developed from this activity for use across all locations in 2008.